2021
DOI: 10.1080/15440478.2021.1961341
|View full text |Cite
|
Sign up to set email alerts
|

A comparative review of Nettle and Ramie fiber and their use in biocomposites, particularly with a PLA matrix

Abstract: Current environmental concerns are increasingly forcing manufacturers to reduce the use of petroleum derivatives in order to reduce their carbon footprint. The use of new plant-based materials is therefore an interesting alternative to plastics. A certain number of plant fibers have been rediscovered for use in the form of agro-composites; Nettle fiber is one of them. The objective of this review is thus to take stock of current knowledge on the European Nettle fiber (Urtica Dioica) and its asian version (Boeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Stinging nettle (Urtica dioica L.) is an erect, herbaceous perennial forb and has been reported to have multiple uses. It is notable for fiber production [27][28][29] and food and medicinal purposes [30,31] and mostly compares with alfalfa in protein content [32,33]. Stinging nettle has been used as a supplement in dried and powdered forms, and is added to the feeds of various animals, including cows for increased milk production [34], horses and pigs for improved health and daily gains [35], as well as feeds for rabbits and captive gorillas [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Stinging nettle (Urtica dioica L.) is an erect, herbaceous perennial forb and has been reported to have multiple uses. It is notable for fiber production [27][28][29] and food and medicinal purposes [30,31] and mostly compares with alfalfa in protein content [32,33]. Stinging nettle has been used as a supplement in dried and powdered forms, and is added to the feeds of various animals, including cows for increased milk production [34], horses and pigs for improved health and daily gains [35], as well as feeds for rabbits and captive gorillas [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…It contains cellulose (68.5–85%), hemicellulose (13.16.7%), and lignin (0.5–0.7%) [ 5 ]. It is renowned for having remarkable luster, strength, durability, low weight, and inherent flame resistance [ 6 , 7 , 8 , 9 ]. Ramie fibers are superior sound insulators and absorbers.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing recognition of the need to look at the various possibilities of combining natural fibers, such as sisal, flax, hemp, and jute with polymer matrices from non-renewable waste plastics to improve the properties of fiber-based composites, as well as for potential structural and non-structural applications [14]. Fabien et al [15] reviewed nettle and ramie fibers and their applications in biocomposites and demonstrated that nettle fibers have special stiffness and strength, which make it completely possible to prepare novel biodegradable composites.…”
Section: Introductionmentioning
confidence: 99%